Sexual Health among Thai Women with Gynecological Problems at a University Hospital - Thanyada Muakkeaw; Bualuang Sumdaengrit; Piyawan Pokpalagon (Clinical and Experimental Obstetrics & Gynecology)
Background: Sexual health is one part of quality of life for women. Those who have gynecological problems may find their sexual health problem, and consequently their quality of life, negatively affected. Thus, the objectives of this study were to: (1) study the sexual health of women with gynecological problems; and (2) compare the sexual health of women with different gynecological problems. Methods: This is a descriptive-comparative study design. Sexual health conceptualization by the World Health Organization was used as a conceptual framework. Data were collected from Thai women with gynecological problems, age 20–59 years, who were actively engaging in sexual intercourse, and who underwent examination at the gynecological outpatient department of a university hospital. Two questionnaires were used: (1) a personal and health status information collection document; and (2) a sexual health questionnaire. The data were analyzed using descriptive statistics, independent t-test, and Mann-Whitney U test in the cases of data that did not meet the assumptions. Results: Two hundred and two women were approached, and 140 consented to participate (69.3% response rate). The results revealed that the age of the participants ranged from 21 to 54 years, with a mean of 36.9 years (standard deviation (SD) = 8.1). The mean score of sexual health problems was 37.3 (SD = 12.1); the score ranged between 0 and 114, with reports of mild (1–38) and moderate/high levels of sexual health problems (>38). In addition, there was a difference in significance between women who had dyspareunia and those who did not (p < 0.000), and between women with paleness/fatigue and those who did not display symptoms (p = 0.004). However, there was no significant difference in sexual health problems between women who suffered abnormal uterine bleeding, dysmenorrhea, or chronic pelvic pain and those who did not. Conclusions: The results of this study can be used as a guideline for providing nursing care to women with gynecological problems, covering all dimensions of sexual health, including reducing other abnormalities and various pains in order to promote sexual health among these women.